Zein/pullulan complex colloidal particle‐stabilized Pickering emulsions for oral delivery of polymethoxylated flavones: protection effect and in vitro digestion. (8th January 2022) - Yu, Yang; Liu, Qian; Wang, Chen; Zhang, Dali; Jiang, Bing; Shan, Yang; Fu, Fuhua; Ding, Shenghua
Abstract: BACKGROUND: Polymethoxylated flavones (PMFs) show multiple biological functions, while their high hydrophobicity leads to a low bioaccessibility and limits their wide applications. The design of a reasonable food‐grade drug delivery system is an effective strategy to improve the low bioaccessibility of PMFs. In this study, sinensetin, tangeretin and nobiletin were encapsulated in Pickering emulsions stabilized by zein/pullulan complex colloidal particles (ZPPs), and the protection effect and in vitro digestion were characterized. RESULTS: Rheological analysis revealed that ZPP–Pickering emulsion loading with PMFs maintained a strong gel‐like network structure. Moreover, the ability to scavenge free radicals of PMFs was improved by the emulsion delivery system. The antioxidant activity of PMFs encapsulated in Pickering emulsion was positively correlated with the oil volume fraction ( φ ). ZPP–Pickering emulsion loading with PMFs can effectively delay lipid oxidation, and the φ (70%) of Pickering emulsion showed the most pronounced effects, in which the lipid hydroperoxide content and malondialdehyde content decreased by 64.3% and 38.3% after 15 days of storage, compared with the bulk oil group, respectively. The bioaccessibility of the three PMFs has been increased by ZPP–Pickering emulsion simultaneously and it presented the highest values as its φ was 50%, in which the bioaccessibility of sinensetin, tangeretin and nobiletin increased by 2.5, 3.2 and 3.9 times, compared with the bulk oil group, respectively. CONCLUSION: Pickering emulsion stabilized by ZPPs is an excellent nutrient delivery system for delivering three PMFs simultaneously and imparting functional properties to bioactive delivery systems. © 2022 Society of Chemical Industry.